The Evolution of the Market Value Definition - Kucharska-Stasiak, Ewa (Geomatics and Environmental Engineering, 2022)
The purpose of the study is the following: (1) indicate the economic sources of the definition of value, including the market value of real estate, (2) present the definition and interpretation of this category, (3) its evolution and the difficult path towards its acceptance in Polish conditions, and (4) identify the reasons for this category being frequently misunderstood in the professional environment. A research hypothesis was put forward that the market value is of a contract nature, its definition and interpretation may change. The study employed a critical analysis of the source literature and legal documents as its methods.